2021
DOI: 10.3390/plants10020275
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptomic Analysis of Gene Expression Inheritance Patterns Associated with Cabbage Head Heterosis

Abstract: The molecular mechanism of heterosis or hybrid vigor, where F1 hybrids of genetically diverse parents show superior traits compared to their parents, is not well understood. Here, we studied the molecular regulation of heterosis in four F1 cabbage hybrids that showed heterosis for several horticultural traits, including head size and weight. To examine the molecular mechanisms, we performed a global transcriptome profiling in the hybrids and their parents by RNA sequencing. The proportion of genetic variations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…We further explored the relationship between cis and/or trans regulatory divergence to patterns of expression inheritance under both water regimens (Table 3 ). First, we classified the mode of inheritance into three broad classes 38 , 39 : additive, dominance, and transgressive. Transgressive mode of inheritance happens when the expression performance of the hybrid is outside the parents’ (illustrated in Rows 1 and 2 of Fig.…”
Section: Heterosismentioning
confidence: 99%
“…We further explored the relationship between cis and/or trans regulatory divergence to patterns of expression inheritance under both water regimens (Table 3 ). First, we classified the mode of inheritance into three broad classes 38 , 39 : additive, dominance, and transgressive. Transgressive mode of inheritance happens when the expression performance of the hybrid is outside the parents’ (illustrated in Rows 1 and 2 of Fig.…”
Section: Heterosismentioning
confidence: 99%
“…Next, we examined how different parental homoeologs contribute to the total gene expression level in the polyploids. In previous studies, ELD, in which the total expression of a gene is similar to one of the parental levels (the “dominant” parent), can be explained by counter‐regulation of the homoeolog from the “non‐dominant” parent (Cox et al., 2014; Li et al., 2021; Li, Liu, et al., 2014; Wu et al., 2018; Yoo et al., 2013), and we observed similar phenomena in the Tragopogon polyploids. As expected, many examples of ELD and transgressive expression were caused by up‐ or down‐regulation of the homoeolog from the other parent (Table S5).…”
Section: Resultsmentioning
confidence: 99%
“…Up to this point our analyses of inheritance patterns cannot discriminate between cis and trans elements; however, allele-specific expression analyses 44 could help to differentiate between them. Using that method in Arabidopsis lyrata hybrids 45 , showed that in the majority of cases genes with maternal effect expressed both parental alleles, while in 17 the authors studied inheritance patterns in cabbage, concluding that cis effects mediate most of the gene expression divergence in the , but also that trans factors appear to have a higher effect compared to cis elements on parental expression divergence. In chili pepper 46 , performed allele-specific expression analyses in a single cross of a domesticated by a wild accession and their in fruits of 40 DAA.…”
Section: Discussionmentioning
confidence: 99%
“…In sunflower heterotic gene pools were developed through the use of crop-wild relatives 14 , and in that paper the authors suggest that there may be underexploited variation within open-pollinated varieties, and thus mining older lines for useful traits could be fruitful. Furthermore, in 15 the authors showed the importance of variation and inheritance of small RNAs in maize inbreds and hybrids, while 16 demonstrated that pathway expression complementation contributes to biomass heterosis in Arabidopsis , while 17 brings new insights into the molecular mechanisms of heterosis during the cabbage head development.…”
Section: Introductionmentioning
confidence: 99%